Alvarado, ūminio uždegiminio atsako, Tzanakio ir RI PASA skalių predikcinė vertė diagnozuojant ūminį apendicitą - Tahir, Senol; Nikolovski, Andrej; Ambardjieva, Martina; Markov, Petar; Mladenovik, Dragoslav; Selim, Gjulsen; Zafirova-Ivanovska, Beti; Janevski, Vlado (Lietuvos chirurgija, 2020)
Introduction. The diagnosis of acute appendicitis (AA), as the most common cause of acute abdominal pain, has changed in the past decade by introducing scoring systems in addition to the use of clinical, laboratory parameters, and radiological examinations. This study aimed to assess the significance of the four scoring systems (Alvarado, Appendicitis Inflammatory Response (AIR), Raya Isteri Pengiran Anak Saleha Appendicitis (RIPASA) and Tzanakis) in the prediction of delayed appendectomy. Materials and methods. The study included 100 respondents, who were diagnosed with AA in the period from January 2018 to February 2019 and were also operated on. In addition to the clinical, laboratory, and ultrasonographic examinations, four scoring systems (Alvarado, AIR, RIPASA, and Tzanakis) were used to diagnose AA. According to the obtained histopathological (HP) findings, the patients were divided into 3 groups: timely appendectomy, delayed appendectomy and unnecessary appendectomy. Using the sensitivity and specificity of all 4 scoring systems, ROC analysis was performed to predict delayed appendectomy. Results. In the study that included 100 patients (58% men, 42% women), after the appendectomy was performed, the resulting HP showed that 74% had a timely appendectomy, while 16% had delayed and 10% had an unnecessary appendectomy. For the prediction of delayed appendectomy, the area under the ROC curve showed a value of 0.577 for the Alvarado score, 0.504 for the AIR, 0.651 for the RIPASA, and 0.696 for the Tzanakis. Sensitivity and specificity for the Alvarado score was 54% and 62%, for RIPASA 62.5% and 63.5%, for Tzanakis 69% and 60.8%, respectively. Combining the three scoring systems (Alvarado, RIPASA, and Tzanakis), the surface area under the ROC curve was 0.762 (95% CI 0.521–0.783), with a sensitivity of 85% and a specificity of 62%. Conclusion. In our study, the diagnostic accuracy of RIPASA and Tzanakis showed better results than Alvarado, while AIR cannot be used to predict delayed appendectomy in our population. However, the simultaneous application of all three scoring systems, RIPASA, Tzanakis and Alvarado, has shown much better discriminatory ability, with higher sensitivity and specificity, as opposed to their use alone. Combining scoring systems should help in proper diagnosis to avoid negative appendectomy, but additional studies with a larger number of patients are needed to support these results.